(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Mg nanoparticles were prepared by PLAL method by placing the element in ionic water with a depth of 3ml and bombarded with a Nd-YAG laser with a wavelength of 1064nm and the number of pulses 100 pulses for each energy (300, 400 and 500) at a fixed frequency of 6hzThe concentration of the elements was calculated by atomic absorption spectrometry (AAS) and the result was (17.4, 27.4, 19.4), respectively. The values of the optical energy gap, which is one of the most important optical constants in semiconductor physics, were calculated by analyzing the UV absorbance spectrum with three concentrations (17.4, 27.4, 19.4), and it was noticed that the higher the concentrations, the lower the energy gap. The particle size was determined by X-ray diffraction (xrd) technique and the crystal size increase of Mgo NPs was observed with increasing laser power by three (111) (220) (331) peaks .The shape of the nanoparticles was known by taking FE-SEM images with a magnification capacity of 330 kx with (300,400,500) mJ, and it shows that they are cube-shaped with different diameters for each sample grouped together with an average size of (100,200,300) respectively of energies (300,400,500) for MgO Nps. The effect of Mgo NPs in the process of inhibiting it was tested against two types of negative bacteria(E. Coli and pseuedomonas aeruginosa) and two types of positive bacteria (s. aurous and streptococcus pyogenes)The sample showed 400 mJ activity against one type of chromosomal bacteria, which is streptococcus pyogenes, with a measure of 22 mm, and a high activity against E. coli (22 mm, 25 mm, 32 mm). And pseudomonas aeruginosa (20mm,28mm,32mm)